Surgical site infection prevention: best practices and new approaches - Abdullah Almottowa, Hisham; Mahzary, Othman Mohammed; Barnawi, Zainab Omar; AlFalah, Danah Ahmad; Albloushi, Fatmah Mousa; Alluhaybi, Amjad MohammedSaad; Aljumaah, Abdulrahman Abdulaziz; Alotaibi, Khalid Turkey; AlMutair, Anas Hamoud; Alharbi, Mazen Abdullah (International Journal Of Community Medicine And Public Health, 2025)
Surgical site infections (SSIs) remain a significant challenge in surgical care, posing a substantial threat to postoperative morbidity and mortality. There are many risk factors that can cause SSIs, encompassing patient-related factors and healthcare team practices. The risk factors for SSIs include advanced age, diabetes, smoking, obesity, distant site infections, elevated biomarkers, low HDL levels, opioid addiction, immunosuppressive drug use, higher ASA grade, comorbidities, prolonged preoperative hospitalization, and antibiotic resistance. Preoperative, intraoperative, and postoperative precautions have all been used as part of comprehensive preventative efforts to reduce the incidence of SSIs. Furthermore, emerging technologies, such as artificial intelligence and machine learning, have demonstrated potential in enhancing SSI detection and prevention, offering promising advancements to further optimize surgical outcomes. This review aims to explore the current evidence, risk factors, and emerging strategies in SSI prevention. By understanding the multifactorial nature of SSIs and implementing comprehensive preventive measures, healthcare providers can significantly mitigate the burden of these infections, ultimately improving patient outcomes and the overall quality of surgical care.